Early Response of Mouse Joint Tissue to Noninvasive Knee Injury Suggests Treatment Targets. Issue 5 (May 2014) - Wu, P.; Holguin, N.; Silva, M. J.; Fu, M.; Liao, W.; Sandell, L. J.
<x xml:space="preserve">Abstract</x> Objective Joint trauma can lead to a spectrum of acute lesions, including cartilage degradation, ligament or meniscus tears, and synovitis, all potentially associated with osteoarthritis (OA). This study was undertaken to generate and validate a murine model of knee joint trauma following noninvasive controlled injurious compression in vivo. Methods The right knees of 8‐week‐old mice were placed in a hyperflexed position and subjected to compressive joint loading at 1 of 3 peak forces (3N, 6N, or 9N) for 60 cycles in a single loading period and harvested on days 5, 9, and 14 after loading (n = 3–5 for each time point and for each loading). The left knees were not loaded and were used as the contralateral control. Histologic, immunohistochemical, and enzyme‐linked immunosorbent assay analyses were performed to evaluate acute pathologic features in chondrocyte viability, cartilage matrix metabolism, synovial reaction, and serum cartilage oligomeric matrix protein (COMP) levels. Results Acute joint pathology was associated with increased injurious loads. All loading regimens induced chondrocyte apoptosis, cartilage matrix degradation, disruption of cartilage collagen fibril arrangement, and increased levels of serum COMP. We also observed that 6N loading induced mild synovitis by day 5, whereas at 9N, with tearing of the anterior cruciate ligament, severe posttraumatic synovitis and ectopic cartilage formation were observed. Conclusion We have established a murine model of knee joint trauma with different degrees of overloading in vivo. Our results suggest that immediate therapies particularly targeted to apoptosis and synovial cell proliferation could affect the acute posttraumatic reaction to potentially limit chronic consequences and OA.